Editorial - Lembert, Anastasia (AIS - Architecture Image Studies, 2024)
As cities worldwide struggle with the imperatives of sustainable development, technological integration, and social resilience, the need for a multifaceted examination of urban reconstruction and development has increased. The collection of articles in this issue represents an effort to bring together diverse perspectives from architecture, urban planning, engineering, and design related to the revitalization, reconstruction, and sustainable development of urban areas worldwide. The COVID-19 pandemic’s context highlighted how global crises impact urban development and construction markets. Articles on digital standards and advanced building technologies were incorporated showing how technological innovation interfaces with traditional urban development challenges. This issue aims to provide readers with a comprehensive understanding of the complex interplay between technological advancement, sustainable development, and human experience in urban environments.